Perkembangan Usaha Rakyat Melalui Lembaga Keuangan Syariah Di Aceh - E Evriyenni (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Efforts to develop the people's business sector continue to be carried out in order to achieve national economic growth. One of the people's businesses that is of concern to the government because it has a contribution to improving the country's economy today is Micro, Small and Medium Enterprises (MSMEs). The implementation of the Dual Banking System in Indonesia provides opportunities for Islamic financial institutions (other than conventional) to play a role in the development of these businesses. The purpose of this study was to determine the role of Islamic financial institutions in the development of people's businesses in Aceh. This research is a qualitative research with descriptive nature. Research informants include MSME actors who obtain business capital assistance from Islamic financial institutions, both Islamic banking and sharia cooperatives. The results showed that MSMEs that received capital assistance in the form of financing/funding from Islamic financial institutions were greatly helped in increasing their business productivity so that they experienced an increase in operating income every year. The capital assistance received also motivates business actors to develop the potential of the leading sector in their respective regions, so as to increase the real sector of the regional economy. This shows that Islamic financial institutions play a very important role in the development of people's businesses, especially in Aceh.